Pengaruh Kepribadian dan Motivasi Berwirausaha terhadap Keberhasilan Berwirausaha (Studi Kasus terhadap Wirausahawan di Kecamatan Sukomanunggal Kota Surabaya Barat) - Sagita, Dini Handayani; Pujianto, Agung; M. Nasution, Ute Chairuz (Research Journal of Social Science and Economics, 2025)
The purpose of this study was to examine the influence of personality and entrepreneurial motivation on entrepreneurial success (a case study of entrepreneurs in Sukomanunggal district, West Surabaya). This type of research is associative using quantitative data analysis methods. The total population is 6,278 people in which the sample determination uses a probability sampling technique of the Simple Random Sampel type, with a total sample of 100 respondents. Data collection techniques in this study used a questionnaire technique which was measured using a Likert scale technique. Then the resulting data will be analyzed using multiple linear regression analysis techniques processed using SPSS. The object of this research is an entrepreneur in Sukomanunggal District, West Surabaya City who is engaged in the Food and Beverage (FnB) sector. The results of the study explain that the respondents’ perceptions of the Personality variable, Entrepreneurial Motivation on Entrepreneurial Success are relatively high. The results of the study also prove that Entrepreneurial Personality and Motivation have a significant and positive influence on Entrepreneurial Success.